Nanette - Gadsby, Hannah (2018)
L'humoriste australienne Hannah Gadsby redéfinit l'humour standard en combinant lignes assassines et révélations troublantes sur les genres, la sexualité et l'enfance.
Keywords: approches et analyses; australie; cours; discours dominant; fem3500; homophobie; hétérosexisme; identités LGBTQIA2+; lesbophobie; océanie; premier cycle; queer; ressource en ligne; régions géographiques; sexisme; systèmes d'oppressions; thématiques; violences

Orchids, intersex and the auto/biographical project - Hart, Phoebe (Studies in Documentary Film, 2013)
Auto/biographical documentaries ask audiences to take a ‘leap of faith’, not being able to offer any real 'proof of the people and events they claim to document, other than that of the film-maker's saying this is what happened. With only memory and history seen through the distorting lens of time, ‘the authenticity of experience functions as a receding horizon of truth in which memory and testimony are articulated as modes of salvage’. Orchids: My Intersex Adventure follows a salvaging of the film-maker's life events and experiences, being born with an intersex condition, and, via the filming and editing process, revolving around the core question: who am I? From this transformative creative documentary practice evolves a new way of embodying experience and ‘seeing’, playfully dubbed here as the ‘intersex gaze’.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; approches et analyses; australie; autoethnographie; cinéma; cinéma documentaire; communication; corps; cours; discipline; discours dominant; identités; intersexuation; inégalités; océanie; premier cycle; périodes historiques; régions géographiques; sexualité; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales